The Effect of Carnitine on Reducing Triglyceride Levels - Thoha, Thoha; Kusniawati, Kusniawati; Subaktio, Toto; Akbar, Roby Rahmadi; Putri, Prystia Riana (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Carnitine is a crucial compound involved in the transport of long-chain fatty acids across mitochondrial membranes, playing an essential role in converting fat into energy. One of the most accessible ways to increase L-carnitine levels is through the consumption of red meat, which is a more affordable alternative compared to supplements. However, there is limited information on the optimal amount of red meat required to reduce blood triglyceride levels. This study aims to compare the effects of 50 mg and 100 mg of L-carnitine derived from red meat on blood triglyceride levels. The research utilized a quantitative approach with a quasi-experimental design. Participants included individuals aged 30-60 years with high triglyceride levels, who consumed beef did not take anti-cholesterol medications or had a history of diabetes. They also agreed to provide blood samples after an 8-9 hour fast. A simple random sampling method was used, with the first and odd-numbered participants assigned to the 100 mg group, and the second and even-numbered participants assigned to the 50 mg group. A total of 38 respondents were involved, with 19 in each group. The results indicated that the mean rank for the 100 mg carnitine group (17.32) was lower than that of the 50 mg group (21.68), though statistical analysis revealed no significant difference in triglyceride reduction between the two doses. The conclusion is the 50 mg carnitine group exhibited a higher increase in triglyceride levels compared to the 100 mg group. These findings suggest that a 12-day intervention with 100 mg of carnitine may prevent an increase in blood triglycerides, while 50 mg may not have the same effect.